Fungsi Keluarga dalam Menerapkan Pola Asuh Terhadap Perkembangan Anak: Tinjauan Al-Qur’an dan Psikologi Perkembangan - Sitti Riadil Jannah; Abu Bakar (JURNAL MAPPESONA, 2025)
This article is the result of a literature research that aims to describe the function of the family in applying parenting to child development through a review of the Qur'an and developmental psychology. The results of the study show that the family plays a central role in shaping the character and development of children. In the perspective of the Qur'an, children are a mandate as well as a test that must be nurtured with responsibility, covering worldly and spiritual aspects. The values of monotheism, morals, and faith are the main basis for building a strong personality. Meanwhile, developmental psychology emphasizes the family as the first environment that influences a child's physical, cognitive, emotional, social, and moral growth. Balanced parenting through affection, discipline, and open communication supports the optimization of children's potential. The harmony of the Qur'an and psychology shows the importance of integrating Islamic values and developmental science in the success of parenting.